Research progress of plant medicine and Chinese herbal compounds in the treatment of rheumatoid arthritis combined with osteoporosis - Gu, Zhuoxu; Zhou, Guanghui; Zhang, Xianquan; Liang, Guihong; Xiao, Xiao; Dou, Yaoxing (Frontiers in Medicine, 2024)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease. The clinical manifestations of various joint pain and bone destruction are common. RA has a high disability rate and is closely related to local and systemic osteoporosis (OP). RA can occur at any age, however, its incidence increases with age. Most patients are 40 to 50 years old with an incidence among women approximately 3 to 5 times more than among men. Osteoporosis is a kind of metabolic bone disease characterized by bone mass and bone microstructure damage and is one of the common complications of RA. Currently, in the clinic, more patients develop RA with OP symptoms. Therefore, both OP and RA-related factors should be considered in the OP treatment of RA. Currently, there is more and more research on RA combined with OP drugs, including basic drugs, bone resorption inhibitors, bone formation promoters, and anti-rheumatic drugs to improve the condition. The high cost or limited efficacy of certain Western drugs, coupled with their potential for adverse reactions during treatment highlight the pressing need for novel pharmaceuticals in clinical practice. In recent years, traditional Chinese medicine (TCM) can improve the bone formation and bone resorption indexes of patients with RA, regulate the balance of osteoclasts and osteoblasts, and regulate the immune inflammatory response, so as to treat RA combined with OP. This article discusses the advancements in single Chinese medicine and Chinese medicine combination treatments for RA complicated with OP, focusing on the mechanism of action and syndrome differentiation and classification, to offer new ideas for future clinical prevention and treatment.